CASE ANALYSIS ON FLIGHT CONTROL SYSTEM SIKORSKY S76 C++ FAILURE FROM YAW CONTROL ASPECT - Rahmawati, Fajar Khanif; Lukito, Indro; Baihaqi, M Imam (Institut Teknologi Dirgantara Adisutjipto, 2022)
Flight Control is a system that functions as a helicopter control center. Failure that occurs in flight control would certainly result inconvenience of the pilot in operating the helicopter, even the movement of the helicopter can out of control causing incident or accident. The continuity of the helicopter operation is affected by the maintenance system applied. One of mode moving system helicopter is yaw control, that could control the nose helicopter to move right and left. Fault Tree Diagram could described analytical technique, whereby an undesired state of the system is specified (usually a state that is critical from a safety or reliability standpoint). The system then analyzed in the context of its environment and operation to find the solution. Based on the analysis results of failures that occurred in the Sikorsky S76 C ++ helicopter flight control from yaw control aspect in the period of January 2015 to May 2018 with an average use of helicopter’s 2092.05 flight hours, there were 46 failures which caused by yaw control. Based on diagram, there were 4 basic events which caused unschedule maintenance on Sikorsky S76 C ++ helicopter flight control system because of yaw fail control, so that a replacement or repair was needed for the components that affected to the system failure.